PENGARUH PENDIDIKAN KESEHATAN BERDASARKAN HEALTH BELIEF MODEL TERHADAP PENGETAHUAN TENTANG PENCEGAHAN KOMPLIKASI PADA PASIEN DIABETES MELLITUS TIPE 2 - Afdita Cynthia Sari; Yesi " Hasneli; Bayhakki " " (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Keperawatan, 2017)
Abstract The purpose of this study was to determine the effect of health education based on Health Belief Model on knowledge about prevention of complications in patients with type 2 diabetes mellitus. This research were conducted in Puskesmas Rejosari Pekanbaru area using quasy eksperimental research design with nonequivalent control group design. Samples of the research were 34 people taken using purposive sampling technique by considering inclusion criteria. The sample was divided into 17 people as the experimental group and 17 people as the control group. The measuring tool used in this study was a questionnaire that has been tested for its validity and reability. The experimental group was given an intervention in the form of health education based on the Health Belief Model on knowledge about prevention of complications in patients with type 2 diabetes mellitus. Analysis used was univariate analysis and bivariate analysis with T dependen test and T independen test. The results showed that respondents most less knowledgeable that as many as 9 people (52,9%) and after being given health education based on Health Belief Model have good knowledge that was as much as 12 people (70,6%). The statistical results obtained p value (0,000) < α (0,05), which mean that there was health education educator based on Health Belief Model to knowledge about prevention of complication at patients type 2 diabetes mellitus. The results of this study are expected to be one of nursing intervention in improving the knowledge of diabetes mellitus patients to prevent complications. Keywords: Type 2 diabetes mellitus, health belief model, knowledge